Transglutaminase is a Critical Link Between Inflammation and Hypertension. Issue 7 (July 2016) - Luo, Renna; Liu, Chen; Elliott, Serra E.; Wang, Wei; Parchim, Nicholas; Iriyama, Takayuki; Daugherty, Patrick S.; Tao, Lijian; Eltzschig, Holger K.; Blackwell, Sean C.; Sibai, Baha M.; Kellems, Rodney E.; et al.
Abstract : Background: The pathogenesis of essential hypertension is multifactorial with different underlying mechanisms contributing to disease. We have recently shown that TNF superfamily member 14 LIGHT (an acronym for homologous to lymphotoxins, exhibits inducible expression, and competes with herpes simplex virus glycoprotein D for herpes virus entry mediator, a receptor expressed by T lymphocytes, also known as TNFSF14) induces hypertension when injected into mice. Research reported here was undertaken to examine the role of transglutaminase (TGase) in LIGHT‐induced hypertension. Methods and Results: Initial experiments showed that plasma and kidney TGase activity was induced by LIGHT infusion (13.91±2.92 versus 6.75±1.92 mU/mL and 19.86±3.55 versus 12.00±0.97 mU/10 μg) and was accompanied with hypertension (169±7.16 versus 117.17±11.57 mm Hg at day 14) and renal impairment (proteinuria, 61.33±23.21 versus 20.38±9.01 μg/mg; osmolality, 879.57±93.02 versus 1407.2±308.04 mmol/kg). The increase in renal TGase activity corresponded to an increase in RNA for the tissue TGase isoform, termed TG2. Pharmacologically, we showed that LIGHT‐induced hypertension and renal impairment did not occur in the presence of cystamine, a well‐known competitive inhibitor of TGase activity. Genetically, we showed that LIGHT‐mediated induction of TGase, along with hypertension and renal impairment, was dependent on interleukin‐6 and endothelial hypoxia inducible factor‐1α. We also demonstrated that interleukin‐6, endothelial hypoxia inducible factor‐1α, and TGase are required for LIGHT‐induced production of angiotensin receptor agonistic autoantibodies. Conclusions: Thus, LIGHT‐induced hypertension, renal impairment, and production of angiotensin receptor agonistic autoantibodies require TGase, most likely the TG2 isoform. Our findings establish TGase as a critical link between inflammation, hypertension, and autoimmunity.